Additional Improvement of Respiratory Technique on Vascular Function in Hypertensive Postmenopausal Women Following Yoga or Stretching Video Classes: The YOGINI Study - Fetter, Cláudia; Marques, Juliana Romeu; de Souza, Liliane Appratto; Dartora, Daniela Ravizzoni; Eibel, Bruna; Boll, Liliana Fortini Cavalheiro; Goldmeier, Sílvia Noll; Dias, Danielle; De Angelis, Katia; Irigoyen, Maria Cláudia (Frontiers in Physiology, 2020)
Background: Hypertension remains highly prevalent in post-menopausal women, along with vascular dysfunction and increased oxidative stress. In such context, regular exercises, yoga practice and slow breathing have been recommended to treat hypertension. However, the effects of the multiple components of yoga, including the respiratory techniques involved in the practice, on hypertension and on vascular and endothelial function have never been evaluated. Objective: This study aimed to investigate the additional effects of respiratory technique on vascular function and oxidative stress profile in hypertensive post-menopausal women (HPMW) following yoga or stretching video classes. Study Design: HPMW were recruited and randomized for 12 weeks, twice a week, of supervised yoga or stretching video classes of 75 minutes for 12 weeks associated or not with respiratory technique. Baseline and post intervention measurements included pulse wave velocity (PWV), flow mediated dilation (FMD), as well as oxidative stress parameters. HPMW (59 ± 0.7 years) who ended the protocol were distributed into three groups: 1) Control Group (Yoga or Stretching, C, n=14); 2) Yoga + respiratory technique (Y+, n=10); 3) Stretching + respiratory technique (S+, n=9). Results: Diastolic blood pressure (DBP) and FMD (baseline- C: 6.94 ± 1.97, Y+: 7.05±1.65 and S+ 3.54±2.01% vs. post- C: 16.59 ± 3.46 (p = 0.006), Y+: 13.72±2.81 (p=0.005) and S+ 11.79±0.99% p=0.0001) have significantly increased in all groups when baseline and post practice values were compared. However, resting heart rate and PWV (baseline- Y+: 10.44±3.69 and S+: 9.50±0.53 m/s vs. post- Y+: 9.45±0.39, p=0.003 and S+: 8.02±0.47 m/s p=0.003) decreased significantly only in Y+ and S+ groups (baseline vs. post). Systemic antioxidant enzyme activities (superoxide dismutase and catalase) increased in all groups and hydrogen peroxide and lipoperoxidation reduced in Y+ and S+ (baseline vs. post). Conclusions: Twelve weeks of yoga or stretching video classes promoted positive changes in several outcomes generally regarded as cardiovascular risk factors in HPMW, and these changes were even more pronounced by the association with respiratory technique.